2009
DOI: 10.1002/fuce.200800082
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Mesoporous Carbons as Catalyst Support for PEM Fuel Cells

Abstract: Preliminary results on Pt‐based electrocatalysts prepared with CMK3 mesoporous carbons are presented. The electro‐catalytic performance towards the oxygen reduction reaction (ORR) was compared to that of commercial Pt/C‐Vulcan catalysts with the same Pt content. Polarisation tests were carried out with a single PEM fuel cell containing the Pt/OMC cathodes. The analysis of these tests, based on a semi‐empirical determination of the various polarisation terms, showed an interesting catalytic activity for ORR for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…It is necessary for the FC power system to cost less than 50$ kW −1 to be technologically competitive and the target for 2015 is 30$ kW −1 [1,4]. Two main approaches in this direction have been the reduction of the Pt loading through dispersion on various carbon supports [5,6] and the use of non-noble metal catalysts [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary for the FC power system to cost less than 50$ kW −1 to be technologically competitive and the target for 2015 is 30$ kW −1 [1,4]. Two main approaches in this direction have been the reduction of the Pt loading through dispersion on various carbon supports [5,6] and the use of non-noble metal catalysts [7].…”
Section: Introductionmentioning
confidence: 99%
“…These porous carbon materials are promising candidates as adsorbents, catalyst supports, electrodes in capacitors, etc. As energy sustainability is a critical global objective, the application of nanoporous carbons (with pore sizes between 2 nm and 100 nm) as supports in the catalyst layers of proton exchange membrane fuel cells (PEMFCs) is of great interest [9][10][11][12][13][14][15][16]. Nanoporous carbons have a large surface area to support the catalyst, normally Pt nanoparticles (3-6 nm), and ideally have pores that are large enough to accommodate Nafion ionomeric clusters (to allow for the transfer of protons) and to facilitate the mass transport of H 2 , O 2 , and water through the catalyst layers [10,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been proposed to prepare Pt catalyst with high surface area. They broadly consists the application of carbon support with high surface area [18] and the control of preparation conditions [19]. For the case of monometallic Pt catalyst, it is reported that not all the exposed surface of Pt to reactant are active for ORR and large portion of them, sometimes more than 45% of total surface area, undergoes oxide poisoning, resulting in the loss of ORR performance [14,21].…”
Section: Introductionmentioning
confidence: 99%